Drivers and outcomes of salespersons’ value opportunity recognition competence in solution selling - Böhm, Eva; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang; Haas, Alexander (Journal of Personal Selling and Sales Management)
Keywords: Management of Technology and Innovation; Human Factors and Ergonomics

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice - Güldenpenning, Iris; Schütz, Christoph; Weigelt, Matthias; Kunde, Wilfried (Psychological Research)
Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specific trial-to-trial adaptations (i.e., congruency sequence effect). Second, we fitted the individual frequency distributions of RTs to ex-Gaussian distributions, to evaluate if practice specifically affects the Gaussian part of the distribution or the exponential part of the distribution. Third, we modeled individual RT distributions as the so-called mixture effects to examine whether the way irrelevant gaze direction impacts performance (either occasionally but massively or continuously but moderately) changes with practice. The analyses revealed that the effect of practice could not be explained with an increasing congruency-sequence effect. Also, it could not be found in the ex-Gaussian distributional analyses. The assumption that residual failure to inhibit the processing of the gaze direction in contrast to continuous failures to do so might favor mixed effects over uniform effects at later courses of practice could not be validated. The reduced head-fake effect thus is argued to source in participants’ general increasing ability to inhibit the processing of the task-irrelevant gaze direction information and/or in a priority shift of gaze processing to a processing of the pass direction.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Social cues can impact complex behavior unconsciously - Schütz, Christoph; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Scientific Reports)
Abstract In three experiments, we investigated the effect of unconscious social priming on human behavior in a choice reaction time task. Photographs of a basketball player passing a ball to the left/right were used as target stimuli. Participants had to respond to the pass direction either by a whole-body (complex) response or a button-press (simple) response. Visually masked stimuli, showing both a task-relevant cue (pass direction) and a task-irrelevant, social cue (gaze direction), were used as primes. Subliminal social priming was found for kinematic (center of pressure) and chronometric measures (response times): gaze direction in the primes affected responses to the pass direction in the targets. The social priming effect diminished when gaze information was unhelpful or even detrimental to the task. Social priming of a complex behavior does not require awareness or intentionality, indicating automatic processing. Nevertheless, it can be controlled by top-down, strategic processes.
Keywords: Multidisciplinary

Head-fake perception in basketball: the relative contributions of expertise, visual or motor training, and test repetition - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (International Journal of Sport and Exercise Psychology)
Keywords: Applied Psychology; Social Psychology

Processing deceptive information in sports: Individual differences for responding to head fakes depends on the attentional capability of the observer - Güldenpenning, Iris; Weigelt, Matthias; Memmert, Daniel; Klatt, Stefanie (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Acta Psychologica)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Negotiating weights for burden sharing rules in international climate negotiations: an empirical analysis - Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Environmental Economics and Policy Studies)
Abstract We have collected data from a world-wide survey among COP delegates to empirically investigate preferences for certain burden sharing rules among key groups in a setting that reflects the possibility of observing concessions from negotiating partners. In our survey, the participants had the opportunity to select and combine up to eight (pre-defined) burden sharing rules and to assign relative weights to the selected rules in their preferred bundle. We examine whether such a mechanism helps to overcome the currently strictly (self-interested) strategic claims on equity in the negotiation process. We observe that delegates from different groups of countries show a general willingness for concessions. However, the degree to which different burden sharing rules are taken into consideration partly differs between countries. As a key insight we report that the individual assessment of the polluter-pays rule based on current emissions does not only stress the persistence of the traditional Annex-B/Non-Annex-B division but also suggests tendencies for a more fragmented grouping with different positions between, for example, delegates from developing countries (i.e. G77 members) and emerging countries (i.e. BASIC). At the same time, we observe tendencies for a more harmonized view among key groups towards the ability-to-pay rule in a setting of weighted burden sharing rules.
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Electrify your game! Anodal tDCS increases the resistance to head fakes in basketball - Friehs, Maximilian A; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)

Valence-dependent changes of neural processing of augmented feedback after extensive practice of a new motor task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Zwischen Trend und Tradition: die Vielfalt des klassischen Gerätturnens und der innovativen Formen des Sichbewegens im Sportunterricht ausgeglichen nutzen. - Köster, Carolin; Kehne, Miriam (Sportpädagogik)

Fitnessstudio Turnhalle : Schülerinnen und Schüler lernen verschiedene Methoden des (hoch-)intensiven Intervalltrainings an klassischen Turngeräten kennen - Köster, Carolin (Sportpädagogik)

Bericht zur 52. Tagung der Arbeitsgemeinschaft für Sportpsychologie: Neues Format, unbekannte Talente und Belohnungsaufschub - Güldenpenning, Iris (Zeitschrift für Sportpsychologie)
Keywords: Applied Psychology; Physical Therapy; Sports Therapy and Rehabilitation; Social Psychology

No effect of social cues in antisocial behavior: The head-fake effect in basketball is not based on the processing of eye gaze direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Y. (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Worauf basiert der Blicktäuschungseffekt im Basketball? Stimulus-Stimulus (S-S) vs. Stimulus-Response (S-R) Interferenz - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

The head-fake effect in basketball is based on the automating processing of head orientation, but not on gaze information - Weigelt, Matthias; Güldenpenning, Iris; Ste, Y. (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball in basketball - Friehs, M.; Güldenpenning, Iris; Frings, C.; Weigelt, Matthias (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Temporal distance between head turn and pass modulates the head fake effect in basketball - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Kunde, W. (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Anpassungseffekte an spielerspezifische Häufigkeiten von Blicktäuschungen im Basketball - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Weigelt, Matthias (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Lernen und Gedächtnis im Sport - Weigelt, Matthias; Krause, Daniel; Güldenpenning, Iris (Sportpsychologie: Grundlagen und Anwendung)

Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Schwingungen - Magnus, Kurt; Popp, Karl; Sextro, Walter
Schwingungsprobleme in der Technik analysieren, verstehen und beschreiben Schwingungen treten als nützliche oder auch als störende Erscheinungen fast überall in Natur und Technik auf. Deshalb ist es wichtig, sie zu verstehen, zu deuten oder auch in gewünschter Weise zu beeinflussen. Dieses Lehrbuch gibt eine Einführung in die physikalischen Grundlagen und die mathematische Behandlung von Schwingungen. In der aktuellen Auflage wurden der Text und die Bilder überarbeitet sowie konstruktive Hinweise von Fachkollegen berücksichtigt. Der Inhalt Grundbegriffe und Darstellungsmittel - Freie Schwingungen - Selbsterregte Schwingungen - Parametererregte Schwingungen - Erzwungene Schwingungen - Koppelschwingungen - Kontinuumsschwingungen - Chaotische Bewegungen - Aufgaben und Ergebnisse Die Zielgruppe Studierende der Ingenieurwissenschaften, der Physik und der Mathematik, berufstätige Ingenieure

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Evaluation of time series forecasting approaches for the reliable crack length prediction of riveted aluminium plates given insufficient data - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (PHM Society European Conference)
In all fields, the significance of a reliable and accurate predictive model is almost unquantifiable. With deep domain knowledge, models derived from first principles typically outperforms other models in terms of reliability and accuracy. When it may become a cumbersome or an unachievable task to build or validate such models of complex (non-linear) systems, machine learning techniques are employed to build predictive models. However, the accuracy of such techniques is not only dependent on the hyper-parameters of the chosen algorithm, but also on the amount and quality of data. This paper investigates the application of classical time series forecasting approaches for the reliable prognostics of technical systems, where black box machine learning techniques might not successfully be employed given insufficient amount of data and where first principles models are infeasible due to lack of domain specific data. Forecasting by analogy, forecasting by analytical function fitting, an exponential smoothing forecasting method and the long short-term memory (LSTM) are evaluated and compared against the ground truth data. As a case study, the methods are applied to predict future crack lengths of riveted aluminium plates under cyclic loading. The performance of the predictive models is evaluated based on error metrics leading to a proposal of when to apply which forecasting approach.
Keywords: PHM 2019; crack propagation; forecasting; unevenly spaced time series; step ahead prediction; short time series

Model-Based Investigation of the Influence of Wheel Suspension Characteristics on Tire Wear - Schütte, Jan; Sextro, Walter (Lecture Notes in Mechanical Engineering)

Evaluating FPGA Accelerator Performance with a Parameterized OpenCL Adaptation of Selected Benchmarks of the HPCChallenge Benchmark Suite - Meyer, Marius; Kenter, Tobias; Plessl, Christian (2020 IEEE/ACM International Workshop on Heterogeneous High-performance Reconfigurable Computing (H2RC))
FPGAs have found increasing adoption in data center applications since a new generation of high-level tools have become available which noticeably reduce development time for FPGA accelerators and still provide high-quality results. There is, however, no high-level benchmark suite available, which specifically enables a comparison of FPGA architectures, programming tools, and libraries for HPC applications. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community.
Keywords: FPGA; OpenCL; High Level Synthesis; HPC benchmarking

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Patent EP 3 358 332 B1: Verfahren zur Bestimmung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer eines elastisch verformbaren Bauteils, als Strukturteil und/oder Lagerteil eines Geräts. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial verformt wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Mess- und Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Beschleunigungssensor, die aktuelle Beschleunigung der Verformung oder daraus abgeleitete Kennwerte als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

The Welfare Conventions Approach: A Comparative Perspective on Social Impact Bonds - Chiapello, Eve; Knoll, Lisa (Journal of Comparative Policy Analysis: Research and Practice)
Keywords: Public Administration; Sociology and Political Science

Social Finance and Impact Investing: Governing Welfare in the Era of Financialization - Chiapello, Eve; Knoll, Lisa (Historical Social Research)

Re/Dissolving Mimesis

A CCTV Image that Dissolves like Smeared Data: Distinguishability versus Similarity - Althoff, Sebastian (Re/Dissolving Mimesis)

Editorial: Re/Dissolving Mimesis - Althoff, Sebastian; Linseisen, Elisa; Müller, Maja-Lisa; Winter, Franziska (Re/Dissolving Mimesis)

Seeping Out: The diminishment of the subject in Hito Steyerl’s How Not to Be Seen - Althoff, Sebastian (Performance Research)

Oracle complexity classes and local measurements on physical Hamiltonians - Gharibian, Sevag; Piddock, Stephen; Yirka, Justin (Proceedings of the 37th Symposium on Theoretical Aspects of Computer Science (STACS 2020))
The canonical problem for the class Quantum Merlin-Arthur (QMA) is that of estimating ground state energies of local Hamiltonians. Perhaps surprisingly, [Ambainis, CCC 2014] showed that the related, but arguably more natural, problem of simulating local measurements on ground states of local Hamiltonians (APX-SIM) is likely harder than QMA. Indeed, [Ambainis, CCC 2014] showed that APX-SIM is P^QMA[log]-complete, for P^QMA[log] the class of languages decidable by a P machine making a logarithmic number of adaptive queries to a QMA oracle. In this work, we show that APX-SIM is P^QMA[log]-complete even when restricted to more physical Hamiltonians, obtaining as intermediate steps a variety of related complexity-theoretic results. We first give a sequence of results which together yield P^QMA[log]-hardness for APX-SIM on well-motivated Hamiltonians: (1) We show that for NP, StoqMA, and QMA oracles, a logarithmic number of adaptive queries is equivalent to polynomially many parallel queries. These equalities simplify the proofs of our subsequent results. (2) Next, we show that the hardness of APX-SIM is preserved under Hamiltonian simulations (a la [Cubitt, Montanaro, Piddock, 2017]). As a byproduct, we obtain a full complexity classification of APX-SIM, showing it is complete for P, P^||NP, P^||StoqMA, or P^||QMA depending on the Hamiltonians employed. (3) Leveraging the above, we show that APX-SIM is P^QMA[log]-complete for any family of Hamiltonians which can efficiently simulate spatially sparse Hamiltonians, including physically motivated models such as the 2D Heisenberg model. Our second focus considers 1D systems: We show that APX-SIM remains P^QMA[log]-complete even for local Hamiltonians on a 1D line of 8-dimensional qudits. This uses a number of ideas from above, along with replacing the "query Hamiltonian" of [Ambainis, CCC 2014] with a new "sifter" construction.

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Resource‐Efficient Low‐Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation - Tan, Deming; Kirbus, Benjamin; Rüsing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M. (Small)
Optically nonlinear Pb2B5O9X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo‐) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low‐cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb 2 B 5 O 9 X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite‐like borate halide structure. Thorough examinations using powder X‐ray diffraction and scanning electron microscopy, the Pb2B5O9X microcrystals are indicated to be chemically pure and single‐phased. Besides, the Pb2B5O9X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low‐temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo‐) catalysis investigations.
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Shallow-etched thin-film lithium niobate waveguides for highly-efficient second-harmonic generation - Zhao, Jie; Rüsing, Michael; Javid, Usman A.; Ling, Jingwei; Li, Mingxiao; Lin, Qiang; Mookherjea, Shayan (Optics Express)
High-fidelity periodic poling over long lengths is required for robust, quasi-phase-matched second-harmonic generation using the fundamental, quasi-TE polarized waveguide modes in a thin-film lithium niobate (TFLN) waveguide. Here, a shallow-etched ridge waveguide is fabricated in x-cut magnesium oxide doped TFLN and is poled accurately over 5 mm. The high fidelity of the poling is demonstrated over long lengths using a non-destructive technique of confocal scanning second-harmonic microscopy. We report a second-harmonic conversion efficiency of up to 939 %/W (length-normalized conversion efficiency 3757 %/Wcm²), measured at telecommunications wavelengths. The device demonstrates a narrow spectral linewidth (1 nm) and can be tuned precisely with a tuning characteristic of 0.1 nm/°C, over at least 40 °C without measurable loss of efficiency.
Keywords: Atomic and Molecular Physics; and Optics

Poling thin-film x-cut lithium niobate for quasi-phase matching with sub-micrometer periodicity - Zhao, Jie; Rüsing, Michael; Roeper, Matthias; Eng, Lukas M.; Mookherjea, Shayan (Journal of Applied Physics)
Quasi-phase-matched grating structures in lithium niobate waveguides with sub-micrometer periodicities will benefit the development of short-wavelength nonlinear optical devices. Here, we report on the reproducible formation of periodically poled domains in x-cut single-crystalline thin-film lithium niobate with periodicities as short as 600 nm. Shaped single-voltage poling pulses were applied to electrode structures that were fabricated by a combination of electron-beam and direct-writing laser lithography. Evidence of successful poling with good quality was obtained through second-harmonic microscopy and piezoresponse force microscopy imaging. For the sub-micrometer period structures, we observed patterns with a double periodicity formed by domain interactions and features with sizes <200 nm.
Keywords: General Physics and Astronomy

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Periodic Poling of X-Cut Thin-Film Lithium Niobate: The Route to Submicrometer Periods - Rüsing, Michael; Roeper, M.; Amber, Z.; Kirbus, B.; Eng, L.M.; Zhao, J.; Mookherjea, S. (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Zwischen romantischem Fragment und Skizze/n der Moderne. Zum medialen Realismus von Wilhelm Raabes "Wer kann es wenden?" - Gretz, Daniela (Jahrbuch der Raabe-Gesellschaft)
Keywords: General Medicine

Towards Real-Time and Unsupervised Campaign Detection in Social Media - Assenmacher, D; Adam, L; Trautmann, Heike; Grimme, C (Proceedings of the Florida Artificial Intelligence Research Society Conference)
The detection of orchestrated and potentially manipulative campaigns in social media is far more meaningful than an- alyzing single account behaviour but also more challenging in terms of pattern recognition, data processing, and com- putational complexity. While supervised learning methods need an enormous amount of reliable ground truth data to find rather inflexible patterns, classical unsupervised learn- ing techniques need a lot of computational power to handle large amount of data. This makes them infeasible for real- time analysis. In this work, we demonstrate the applicability of text stream clustering for the real-time detection of coordi- nated campaigns.

Die Tageszeitung des 18. Jahrhunderts auf dem Weg zum Massenmedium - Wille, Manuel
In der Forschungsarbeit wird die Zeitungskommunikation des 18. Jahrhunderts aus sprachwissenschaftlicher Perspektive untersucht. Es wird gezeigt, wie sich das Textsortenrepertoire der Zeitung weiterentwickelte, welche sprachlichen Wandelprozesse stattfanden und wie die Zeitung übergreifend allmählich zu einem Massenmedium avancierte. Der textlinguistische Zugang auf die Zeitungssprache wird an den relevanten Stellen ergänzt durch einschlägige Erkenntnisse aus der historischen Presseforschung und der linguistischen Kulturanalyse. So wird etwa nachgezeichnet, wie sich die Zeitungsschreiber im Laufe des Jahrhunderts immer stärker von den Einflüssen der Kanzleisprachen lösten und Formulierungsstrategien etablierten, die auf die Anforderungen des journalistischen Berichtens abgestimmt waren. Mit diesen und weiteren Ergebnissen wird der Versuch angestellt, eine Forschungslücke der Sprachgeschichtsforschung zu schließen, in der die Zeitungen des 18. Jahrhunderts bisher lediglich randständig untersucht wurden.
Keywords: text linguistics; newspaper; Hamburgischer Correspondent; Textlinguistik; Sprachgeschichte; Textsortenwandel; Korpuslinguistik

Pressesprache - Wille, Manuel (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online, edited by Stefan J. Schierholz.)

Zeitungsstil - Wille, Manuel (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online, edited by Stefan J. Schierholz.)

So Far...From Now On # 6. - Jacke, Christoph (Die Aufhebung)

Statistical and Neural Network Based Speech Activity Detection in Non-Stationary Acoustic Environments - Heitkaemper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (INTERSPEECH 2020 Virtual Shanghai China)
Speech activity detection (SAD), which often rests on the fact that the noise is "more'' stationary than speech, is particularly challenging in non-stationary environments, because the time variance of the acoustic scene makes it difficult to discriminate speech from noise. We propose two approaches to SAD, where one is based on statistical signal processing, while the other utilizes neural networks. The former employs sophisticated signal processing to track the noise and speech energies and is meant to support the case for a resource efficient, unsupervised signal processing approach. The latter introduces a recurrent network layer that operates on short segments of the input speech to do temporal smoothing in the presence of non-stationary noise. The systems are tested on the Fearless Steps challenge database, which consists of the transmission data from the Apollo-11 space mission. The statistical SAD achieves comparable detection performance to earlier proposed neural network based SADs, while the neural network based approach leads to a decision cost function of 1.07% on the evaluation set of the 2020 Fearless Steps Challenge, which sets a new state of the art.
Keywords: voice activity detection; speech activity detection; neural network; statistical speech processing

When entrepreneurs become leaders: how entrepreneurs deal with people management - Hubner-Benz, Sylvia (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Hustlers, hipsters and hackers: Potential employees’ stereotypes of entrepreneurial leaders - Rudic, Biljana; Hubner-Benz, Sylvia; Baum, Matthias (Journal of Business Venturing Insights)
Keywords: Management of Technology and Innovation; Business and International Management

Perceptions of the Self Versus One’s Own Social Group: (Mis)conceptions of Older Women’s Interest in and Competence With Technology - Gales, Alina; Hubner-Benz, Sylvia (Frontiers in Psychology)
Keywords: General Psychology

Political embeddedness and firms’ choices of earnings management strategies in China - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin (Accounting & Finance)
Abstract We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms’ choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs’ total earnings management level is higher than that of non‐PCEs.
Keywords: Economics; Econometrics and Finance (miscellaneous); Finance; Accounting

Bringing Signaling Theory to Intermediated Voluntary Disclosure. Commentary on “Detecting False Accounts in Intermediated Voluntary Disclosure” by Patrick Callery and Jessica Perkins - Hahn, Rüdiger; Reimsbach, Daniel (Academy of Management Discoveries)

Enhancing Fifth Graders’ Awareness of Syntactic Features in Mathematical Word Problems: A Design Research Study on the Variation Principle - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik, 41(2))

Symmetry in optimal control: A multiobjective model predictive control approach - Flaßkamp, K.; Ober-Blöbaum, Sina; Peitz, S. (Advances in Dynamics, Optimization and Computation)

"Dein jüdisches Gesicht". Zu drei Gedichten des "Ilana"-Zyklus von Paul Celan - Spener, Anna Maria (Celan-Jahrbuch 11)

Automatisierung der motorischen Kontrolle - Krause, Daniel; Blischke, Klaus (Bewegung, Training, Leistung und Gesundheit)

Is it still worth it? Applying expectancy-value theory to investigate the intraindividual motivational process of forming intentions to drop out from university - Schnettler, Theresa; Bobe, Julia; Scheunemann, Anne; Fries, Stefan; Grunschel, Carola (Motivation and Emotion)
Abstract The intraindividual process of study dropout, from forming dropout intention to deregistration, is of motivational nature. Yet typical studies investigate interindividual differences, which do not inform about intraindividual processes. Our study focused on the intraindividual process of forming dropout intention, and applied expectancy-value theory to analyze its motivational underpinnings. To expand research, we considered associations of intraindividual deviations in expectancy, intrinsic value, attainment value, utility value, and cost to intraindividual deviations in dropout intention. A total of 326 undergraduate students of law and mathematics rated motivational variables and dropout intention three times from semester start to the final exam period. Multilevel regression analyses revealed that intraindividual changes in intrinsic value, attainment, and cost, but not in expectancy and utility, related to intraindividual changes in dropout intention. Further, we considered students’ demographics as moderators. Only age moderated the association between intrinsic value and dropout intention. Our results stress the crucial role of certain value components, including cost, for emerging dropout intention.
Keywords: Experimental and Cognitive Psychology; Social Psychology

End-to-End Training of Time Domain Audio Separation and Recognition - von Neumann, Thilo; Kinoshita, Keisuke; Drude, Lukas; Boeddeker, Christoph; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
The rising interest in single-channel multi-speaker speech separation sparked development of End-to-End (E2E) approaches to multispeaker speech recognition. However, up until now, state-of-theart neural network–based time domain source separation has not yet been combined with E2E speech recognition. We here demonstrate how to combine a separation module based on a Convolutional Time domain Audio Separation Network (Conv-TasNet) with an E2E speech recognizer and how to train such a model jointly by distributing it over multiple GPUs or by approximating truncated back-propagation for the convolutional front-end. To put this work into perspective and illustrate the complexity of the design space, we provide a compact overview of single-channel multi-speaker recognition systems. Our experiments show a word error rate of 11.0% on WSJ0-2mix and indicate that our joint time domain model can yield substantial improvements over cascade DNN-HMM and monolithic E2E frequency domain systems proposed so far.

Multi-Talker ASR for an Unknown Number of Sources: Joint Training of Source Counting, Separation and ASR - von Neumann, Thilo; Boeddeker, Christoph; Drude, Lukas; Kinoshita, Keisuke; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (Proc. Interspeech 2020)
Most approaches to multi-talker overlapped speech separation and recognition assume that the number of simultaneously active speakers is given, but in realistic situations, it is typically unknown. To cope with this, we extend an iterative speech extraction system with mechanisms to count the number of sources and combine it with a single-talker speech recognizer to form the first end-to-end multi-talker automatic speech recognition system for an unknown number of active speakers. Our experiments show very promising performance in counting accuracy, source separation and speech recognition on simulated clean mixtures from WSJ0-2mix and WSJ0-3mix. Among others, we set a new state-of-the-art word error rate on the WSJ0-2mix database. Furthermore, our system generalizes well to a larger number of speakers than it ever saw during training, as shown in experiments with the WSJ0-4mix database.

Gedenken an Luftangriffe auf Paderborn: "Erinnerung wird nie obsolet sein" - Hartung, Olaf (Neue Westfälische)

Workshops zur geschichtsdidaktischen Lehre in Zeiten von Corona - Hartung, Olaf (Paderborner Universitätszeitschrift)

Deep Neural Network based Distance Estimation for Geometry Calibration in Acoustic Sensor Network - Gburrek, Tobias; Schmalenstroeer, Joerg; Brendel, Andreas; Kellermann, Walter; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))
We present an approach to deep neural network based (DNN-based) distance estimation in reverberant rooms for supporting geometry calibration tasks in wireless acoustic sensor networks. Signal diffuseness information from acoustic signals is aggregated via the coherent-to-diffuse power ratio to obtain a distance-related feature, which is mapped to a source-to-microphone distance estimate by means of a DNN. This information is then combined with direction-of-arrival estimates from compact microphone arrays to infer the geometry of the sensor network. Unlike many other approaches to geometry calibration, the proposed scheme does only require that the sampling clocks of the sensor nodes are roughly synchronized. In simulations we show that the proposed DNN-based distance estimator generalizes to unseen acoustic environments and that precise estimates of the sensor node positions are obtained.

Corporate Entrepreneurship: Die Rolle und Bedeutung des Humankapitals - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Corporate Entrepreneurship durch die Allokation von Ressourcen - Megow, N.; Kabst, Rüdiger (Perspektiven des Entrepreneurships: Unternehmerische Konzepte zwischen Theorie und Praxis)

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie; Furman, Susanne; Acar, Yasemin

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie M.; Furman, Susanne M.; Acar, Yasemin (HCI for Cybersecurity, Privacy and Trust)

Cloudy with a Chance of Misconceptions: Exploring Users’ Perceptions and Expectations of Security and Privacy in Cloud Office Suites - Wermke, Dominik; Huaman, Nicolas; Stransky, Christian; Busch, Niklas; Acar, Yasemin; Fahl, Sascha (Sixteenth Symposium on Usable Privacy and Security, SOUPS 2020, August 7-11, 2020)

Listen to Developers! A Participatory Design Study on Security Warnings for Cryptographic APIs - Gorski, Peter Leo; Acar, Yasemin; Lo Iacono, Luigi; Fahl, Sascha (Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems)

Gier und andere Tugenden: Widersprüchliche Bewertungen der Marktwirtschaft in Oliver Stones Wall Street - Schneider, Martin (Erzähltes Geld Finanzmärkte und Krisen in Literatur, Film und Medien)

Urbane Arbeitsparadiese gestern und heute - Schneider, Martin (Urbane Kulturen und Räume Intermedial)

Personalwirtschaft - Schneider, Martin; Eisele, Simon (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)

Is Corruption Imprinted? A Study on Preconditions of Corruption in Post-Communist Countries - Knorr, Karin; Auer, Thorsten Fabian; Thommes, Kirsten (Academy of Management Proceedings)

»die reine farben- formen- und linienfreude«. Zur Vision einer ›reinen Formkunst‹ in den ornamentalen Konstellationen der Blätter für die Kunst - Gretz, Daniela (Formästhetiken und Formen der Literatur. Materialität – Ornament – Codierung)

Expertise von Lehrpersonen für inklusiven Mathematikunterricht der Sekundarstufe - Ausgangspunkte zur Professionalisierungsforschung. - Seitz, Susanne; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (K:ON Kölner Online-Journal für Lehrer*innenbildung)

Wolfgang Weber (1939–2019) Professor of Human Resource Management and Founding Editor of the German Journal of Human Resource Management - Festing, Marion; Iseke, Anja; Kabst, Rüdiger; Martin, Albert; Matiaske, Wenzel; Mayrhofer, Wolfgang; Nienhüser, Werner (German Journal of Human Resource Management: Zeitschrift für Personalforschung)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Social Sciences (miscellaneous)

Ecken, Systeme, Funktionsbereiche. Eine Medienkulturgeschichte des Filter(n)s im Kontext von Wohnräumen - Miggelbrink, Monique (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften, Themenschwerpunkt: Filter(n) – Geschichte Ästhetik Praktiken)

Nash Smoothing on the Test Bench: H_alpha--Essential Equilibira - Duman, Papatya; Trockel, Walter

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, José Angelo; Figueiredo, Gabriella Andreeta; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: A detail of previous studies on mental rotation, which has not received any attention so far, relates to the testing situation of the participants. In nearly every study, participants were tested in a sitting posture (and not standing). However, when considering embodied cognition approaches on mental processes, participants may not be able to fully exploit these processes when performing mental rotation tasks in a sitting posture.
AIM: Therefore, the aim of the present study is to examine the potential influence of two different postures (sitting vs. standing), when solving mental body rotation tasks.
METHOD: Sixteen participants (6 females) were tested in two mental body-rotation tasks (MBRT), requiring either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment) in a sitting and in a standing posture. Reaction times and response errors were analysed in two three-way ANOVAs, with the factors orientation, task, and posture.
RESULTS: Results revealed an effect of orientation and task, indicating that participants performed better for egocentric than for object-based transformations. However, there was no effect of posture.
CONCLUSION: The different dynamics of postural control during sitting and standing do not induce different embodiment effects on mental rotation.

Hat die Körperposition (sitzen vs. stehen) einen Einfluss auf die Leistung in einer Mentalen Rotationsaufgabe? - Budde, Kirsten; Barela, José A; Weigelt, Matthias (Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Linguistik des Briefs - Schuster, Britt-Marie (Handbuch Brief. Von der Frühen Neuzeit bis zur Gegenwart (Bd. 1: Interdisziplinarität – Systematische Perspektiven – Briefgenres))
Keywords: Textsortengeschichte

The contribution of terminology research to the understanding of science communication - Schuster, Britt-Marie (Science Communication (Handbooks of Communication Science))
Keywords: Fachkommunikation

Was bedeutet Ehre? Diskursethische Überlegungen zu den BBC-Reden Thomas Manns - Schuster, Britt-Marie; Markewitz, Friedrich; Wilk, Nicole M. (Diskurs – ethisch.)
Keywords: Textsemantik

micro-Raman Investigations of Periodically-Poled X-Cut Thin-Film Lithium Niobate for Integrated Optics - Reitzig, Sven; Rüsing, Michael; Kirbus, Benjamin; Gossel, Joshua; Singh, Ekta; Eng, Lukas M.; Zhao, Jie; Mookherjea, Shayan (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

Selbstreguliertes Lernen - Können die das überhaupt? Gestaltung von Lernprozessen in berufsvorbereitenden Bildungsgängen. - Sloane, Peter F. E.; Daniel, Desiree; Meier, Karin; Schwabl, Franziska; Volgmann, Simone

Per-Instance Configuration of the Modularized CMA-ES by Means of Classifier Chains and Exploratory Landscape Analysis - Prager, Raphael Patrick; Trautmann, Heike; Wang, Hao; Bäck, Thomas H. W.; Kerschke, Pascal (Proceedings of the IEEE Symposium Series on Computational Intelligence (SSCI))
In this paper, we rely on previous work proposing a modularized version of CMA-ES, which captures several alterations to the conventional CMA-ES developed in recent years. Each alteration provides significant advantages under certain problem properties, e.g., multi-modality, high conditioning. These distinct advancements are implemented as modules which result in 4608 unique versions of CMA-ES. Previous findings illustrate the competitive advantage of enabling and disabling the aforementioned modules for different optimization problems. Yet, this modular CMA-ES is lacking a method to automatically determine when the activation of specific modules is auspicious and when it is not. We propose a well-performing instance-specific algorithm configuration model which selects an (almost) optimal configuration of modules for a given problem instance. In addition, the structure of this configuration model is able to capture inter-dependencies between modules, e.g., two (or more) modules might only be advantageous in unison for some problem types, making the orchestration of modules a crucial task. This is accomplished by chaining multiple random forest classifiers together into a so-called Classifier Chain based on a set of numerical features extracted by means of Exploratory Landscape Analysis (ELA) to describe the given problem instances.

A Two-Phase Framework for Detecting Manipulation Campaigns in Social Media - Assenmacher, D; Clever, L; Pohl, JS; Trautmann, Heike; Grimme, C (Proceedings of the International Conference on Human-Computer Interaction (HCII 2020): Social Computing and Social Media. Design, Ethics, User Behavior, and Social Network Analysis)
The identification of coordinated campaigns within Social Media is a complex task that is often hindered by missing labels and large amounts of data that have to be processed. We propose a new two-phase framework that uses unsupervised stream clustering for detecting suspicious trends over time in a first step. Afterwards, traditional offline analyses are applied to distinguish between normal trend evolution and malicious manipulation attempts. We demonstrate the applicability of our framework in the context of the final days of the Brexit in 2019/2020.

Towards Automated Configuration of Stream Clustering Algorithms - Carnein, Matthias; Trautmann, Heike; Bifet, Albert; Pfahringer, Bernhard (Proceedings of the European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases (ECMLPKDD ’19))
Clustering is an important technique in data analysis which can reveal hidden patterns and unknown relationships in the data. A common problem in clustering is the proper choice of parameter settings. To tackle this, automated algorithm configuration is available which can automatically find the best parameter settings. In practice, however, many of our today’s data sources are data streams due to the widespread deployment of sensors, the internet-of-things or (social) media. Stream clustering aims to tackle this challenge by identifying, tracking and updating clusters over time. Unfortunately, none of the existing approaches for automated algorithm configuration are directly applicable to the streaming scenario. In this paper, we explore the possibility of automated algorithm configuration for stream clustering algorithms using an ensemble of different configurations. In first experiments, we demonstrate that our approach is able to automatically find superior configurations and refine them over time.

Inside the tool set of automation: Free social bot code revisited - Assenmacher, Dennis; Frischlich , Lena; Trautmann, Heike; Grimme, Christian; Adam, Lena (Disinformation in open online media)
Social bots have recently gained attention in the context of public opinion manipulation on social media platforms. While a lot of research effort has been put into the classification and detection of such automated programs, it is still unclear how technically sophisticated those bots are, which platforms they target, and where they originate from. To answer these questions, we gathered repository data from open source collaboration platforms to identify the status-quo of social bot development as well as first insights into the overall skills of publicly available bot code.

confStream: Automated Algorithm Selection and Configuration of Stream Clustering Algorithms - Carnein, Matthias; Trautmann, Heike; Bifet, Albert; Pfahringer, Bernhard (Proceedings of the 14$^th$ Learning and Intelligent Optimization Conference (LION 2020))
Machine learning has become one of the most important tools in data analysis. However, selecting the most appropriate machine learning algorithm and tuning its hyperparameters to their optimal values remains a difficult task. This is even more difficult for streaming applications where automated approaches are often not available to help during algorithm selection and configuration. This paper proposes the first approach for automated algorithm selection and configuration of stream clustering algorithms. We train an ensemble of different stream clustering algorithms and configurations in parallel and use the best performing configuration to obtain a clustering solution. By drawing new configurations from better performing ones, we are able to improve the ensemble performance over time. In large experiments on real and artificial data we show how our ensemble approach can improve upon default configurations and can also compete with a-posteriori algorithm configuration. Our approach is considerably faster than a-posteriori approaches and applicable in real-time. In addition, it is not limited to stream clustering and can be generalised to all streaming applications, including stream classification and regression.

Anytime Behavior of Inexact TSP Solvers and Perspectives for Automated Algorithm Selection - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Proceedings of the IEEE Congress on Evolutionary Computation (CEC))
The Traveling-Salesperson-Problem (TSP) is arguably one of the best-known NP-hard combinatorial optimization problems. The two sophisticated heuristic solvers LKH and EAX and respective (restart) variants manage to calculate close-to optimal or even optimal solutions, also for large instances with several thousand nodes in reasonable time. In this work we extend existing benchmarking studies by addressing anytime behaviour of inexact TSP solvers based on empirical runtime distributions leading to an increased understanding of solver behaviour and the respective relation to problem hardness. It turns out that performance ranking of solvers is highly dependent on the focused approximation quality. Insights on intersection points of performances offer huge potential for the construction of hybridized solvers depending on instance features. Moreover, instance features tailored to anytime performance and corresponding performance indicators will highly improve automated algorithm selection models by including comprehensive information on solver quality.

Towards Decision Support in Dynamic Bi-Objective Vehicle Routing - Bossek, Jakob; Grimme, Christian; Rudolph, Günter; Trautmann, Heike (Proceedings of the IEEE Congress on Evolutionary Computation (CEC))
We consider a dynamic bi-objective vehicle routing problem, where a subset of customers ask for service over time. Therein, the distance traveled by a single vehicle and the number of unserved dynamic requests is minimized by a dynamic evolutionary multi-objective algorithm (DEMOA), which operates on discrete time windows (eras). A decision is made at each era by a decision-maker, thus any decision depends on irreversible decisions made in foregoing eras. To understand effects of sequences of decision-making and interactions/dependencies between decisions made, we conduct a series of experiments. More precisely, we fix a set of decision-maker preferences D and the number of eras n t and analyze all |D| nt combinations of decision-maker options. We find that for random uniform instances (a) the final selected solutions mainly depend on the final decision and not on the decision history, (b) solutions are quite robust with respect to the number of unvisited dynamic customers, and (c) solutions of the dynamic approach can even dominate solutions obtained by a clairvoyant EMOA. In contrast, for instances with clustered customers, we observe a strong dependency on decision-making history as well as more variance in solution diversity.

Dynamic Bi-Objective Routing of Multiple Vehicles - Bossek, Jakob; Grimme, Christian; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’20))
In practice, e.g. in delivery and service scenarios, Vehicle-Routing-Problems (VRPs) often imply repeated decision making on dynamic customer requests. As in classical VRPs, tours have to be planned short while the number of serviced customers has to be maximized at the same time resulting in a multi-objective problem. Beyond that, however, dynamic requests lead to the need for re-planning of not yet realized tour parts, while already realized tour parts are irreversible. In this paper we study this type of bi-objective dynamic VRP including sequential decision making and concurrent realization of decisions. We adopt a recently proposed Dynamic Evolutionary Multi-Objective Algorithm (DEMOA) for a related VRP problem and extend it to the more realistic (here considered) scenario of multiple vehicles. We empirically show that our DEMOA is competitive with a multi-vehicle offline and clairvoyant variant of the proposed DEMOA as well as with the dynamic single-vehicle approach proposed earlier.

Automated detection of nostalgic text in the context of societal pessimism - Lena, Clever; Frischlich, Lena; Trautmann, Heike; Grimme, Christian (Disinformation in open online media)
In online media environments, nostalgia can be used as important ingredient of propaganda strategies, specifically, by creating societal pessimism. This work addresses the automated detection of nostalgic text as a first step towards automatically identifying nostalgia-based manipulation strategies. We compare the performance of standard machine learning approaches on this challenge and demonstrate the successful transfer of the best performing approach to real-world nostalgia detection in a case study.

Deep Learning as a Competitive Feature-Free Approach for Automated Algorithm Selection on the Traveling Salesperson Problem - Seiler, Moritz V; Pohl, Janina; Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Proceedings of the 16$^th$ International Conference on Parallel Problem Solving from Nature (PPSN XVI))
In this work we focus on the well-known Euclidean Traveling Salesperson Problem (TSP) and two highly competitive inexact heuristic TSP solvers, EAX and LKH, in the context of per-instance algorithm selection (AS). We evolve instances with 1000 nodes where the solvers show strongly different performance profiles. These instances serve as a basis for an exploratory study on the identification of well-discriminating problem characteristics (features). Our results in a nutshell: we show that even though (1) promising features exist, (2) these are in line with previous results from the literature, and (3) models trained with these features are more accurate than models adopting sophisticated feature selection methods, the advantage is not close to the virtual best solver in terms of penalized average runtime and so is the performance gain over the single best solver. However, we show that a feature-free deep neural network based approach solely based on visual representation of the instances already matches classical AS model results and thus shows huge potential for future studies.

Building an Integrated Comment Moderation System – Towards a Semi-automatic Moderation Tool - Riehle, Dennis M.; Niemann, Marco; Brunk, Jens; Assenmacher, Dennis; Trautmann, Heike; Becker, Jörg (Social Computing and Social Media. Participation, User Experience, Consumer Experience, and Applications of Social Computing)
The past decade has been characterized by a strong increase in the use of social media and a continuous growth of public online discussion. With the failure of purely manual moderation, platform operators started searching for semi-automated solutions, where the application of Natural Language Processing (NLP) and Machine Learning (ML) techniques is promising. However, this requires huge financial investments for algorithmic implementations, data collection, and model training, which only big players can afford. To support smaller or medium-sized media enterprises (SME), we developed an integrated comment moderation system as an IT platform. This platform acts as a service provider and offers Analytics as a Service (AaaS) to SMEs. Operating such a platform, however, requires a robust technology stack, integrated workflows and well-defined interfaces between all parties. In this paper, we develop and discuss a suitable IT architecture and present a prototypical implementation.

Demystifying Social Bots: On the Intelligence of Automated Social Media Actors - Assenmacher, Dennis; Clever, Lena; Frischlich, Lena; Quandt, Thorsten; Trautmann, Heike; Grimme, Christian (Social Media + Society)
Recently, social bots, (semi-) automatized accounts in social media, gained global attention in the context of public opinion manipulation. Dystopian scenarios like the malicious amplification of topics, the spreading of disinformation, and the manipulation of elections through “opinion machines” created headlines around the globe. As a consequence, much research effort has been put into the classification and detection of social bots. Yet, it is still unclear how easy an average online media user can purchase social bots, which platforms they target, where they originate from, and how sophisticated these bots are. This work provides a much needed new perspective on these questions. By providing insights into the markets of social bots in the clearnet and darknet as well as an exhaustive analysis of freely available software tools for automation during the last decade, we shed light on the availability and capabilities of automated profiles in social media platforms. Our results confirm the increasing importance of social bot technology but also uncover an as yet unknown discrepancy of theoretical and practically achieved artificial intelligence in social bots: while literature reports on a high degree of intelligence for chat bots and assumes the same for social bots, the observed degree of intelligence in social bot implementations is limited. In fact, the overwhelming majority of available services and software are of supportive nature and merely provide modules of automation instead of fully fledged “intelligent” social bots.